A new species of Epidendrum (Orchidaceae: Laeliinae) of the Incomptum group from the north of Antioquia, Colombia - Rincón-González, Milton (2024)
A new species of Epidendrum of the Incomptum group is described and illustrated, so far found only from the type locality. Information is provided to separate between the species belonging to the Arbuscula and Incomptum groups. Moreover, the new taxon described here, Epidendrum pembertonii, is thoroughly compared with the four most morphologically similar species (E. brenesii, E. bisulcatum, E. foldatsii, E. sotoanum), showing notable differences in the number and shape of leaves, inflorescence length, color of flowers, sepals venation, shape and ornamentation of the lip and column.